Penerapan Algoritma K-Nearest Neighbor Untuk Pengelolaan Efisien Tata Letak Buku Dalam Lingkungan Perpustakaan - Dzulfikri Akbar Dollar; Ilka Zufria (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
The library plays a central role in providing efficient access to information tailored to the interests of the community. The current system of organizing the library at the Medan City Library and Archives Department involves using call numbers. This system isn't very efficient for readers looking for interesting books, which can decrease people's interest in reading and perceive the library as a dull place. Hence, researchers have attempted to optimize book layout by prioritizing the most popular books. Using the K-Nearest Neighbor algorithm to optimize the book layout at the Medan City Library and Archives Department can assist in arranging book patterns based on historical borrowing data and facilitate better access to collections favored by library visitors. The research method involves collecting book borrowing data from previous months and processing it using the K-Nearest Neighbor Algorithm with Euclidean Distance calculation. The research results demonstrate that implementing this algorithm successfully predicts book arrangement patterns that align with reader interests. An adaptively arranged layout enhances the availability of popular books in easily accessible areas of the library for visitors. This is evident from the research findings in May, where the priority for the following month was the general collection. Similarly, in June, the priority was indeed the general collection, confirming that the algorithm's use of K-Nearest Neighbor is successful in optimizing book layout.